Alignment of innovation diffusion and project management to increase logistics digitalization - Daškevič, Diana; Burinskienė, Aurelija (Business, Management and Economics Engineering, 2025)
Purpose – This paper examines how integrating Innovation Diffusion Theory (IDT)  with structured project management frameworks enhances digital technology adoption in  logistics, addressing challenges in ineffective implementation.Research methodology – A mixed-methods approach combines qualitative interviews with  logistics executives and technology experts with quantitative analysis of adoption trends using case studies and industry data. Findings – Results highlight the complexity of digital technologies and emphasize aligning  decision-making frameworks – Agile, Scrum, Kanban, and Waterfall – with organizational goals  to improve digital transformation. Structured project management methodologies help firms manage complexity, mitigate risks, and optimize project execution.Research limitations – The study does not analyze all technology complexity levels or include  all digital solutions in logistics. Additionally, not all technologies were linked to expert-identified success factors, limiting generalizability. Future research could use longitudinal or case-study approaches to explore long-term impacts.Practical implications – Integrating IDT with project management frameworks and the Stacey Matrix helps logistics firms overcome adoption barriers and improve implementation success. Originality/Value – This research provides empirical evidence on structured decision-making in digital adoption. By integrating expert insights and correlation analysis, it offers practical recommendations for optimizing innovation diffusion, mitigating risks, and aligning technology implementation with strategic goals in a rapidly evolving digital landscape.